Kurikulum PAI Aktual dan Ideal di MIN 4 Rejang Lebong - Yosita, Yosita; Wanto, Deri (Jurnal Pendidikan Guru, 2023)
Madrasah are schools that emphasize the value of Islamic religious teachings compared to other public schools. Madrasah also play a role in creating civilized and Islamic generations. So Madrasah are required to be able to provide effective and efficient learning of Islamic religious education to students and be able to answer the wishes of the surrounding community. So that Madrasah should be able to develop an actual and ideal Islamic religious education curriculum. Including Madrasah Ibtidaiyah Negeri 4 Rejang Lebong also has the same challenges. The condition of the community around the Rejang Lebong 4 Public Elementary School which is lagging behind in moral values is a big task for the madrasa in providing Islamic religious education to its students. So the Rejang Lebong 4 Public Elementary School tries to apply the actual and ideal curriculum. This is a real form of effort made by the madrasa in shaping and changing student behavior and fortifying students against negative things from the environment around students. In the process the teacher arranges learning administration in the form of a syllabus, lesson plan, annual program and semester program. Teachers use technology in learning. Teachers carry out exemplary-based programs. The commemoration of Islamic holidays is used as a moment to convey noble moral teachings to students